Factores de riesgo psicosociales y ambientales asociados a trastornos mentales (2010)
ABSTRACT: In Colombia, there are few studies on the association of psychosocial and environmental factors with the most prevalent mental disorders; such studies are important due to the context of violence, social insecurity, and job and economic instability in the country. The objective of this study was to identify the psychosocial and environmental risk factors for mental disorders, in users of psychological services in Colombia. The Mini International Neuropsychiatric Interview and a Questionnaire to evaluate the Axis-IV of the DSM-IV-TR were applied to 490 participants. The analysis comprised descriptive statistics and risk factors. As risk factors for depression, there were identified housing problems, access to health care services, problems related to the primary group, economics, problems of the social environment, and labor. For generalized anxiety, there were identified economic and education issues. For panic disorders, the risk factors were related to social environment, and for social phobia, the risk factors were problems in education, work and social environment.